Seasonal variations of heavy metal concentrations in tissues of Talang Queenfish (Scomberoides commersonianus) from Iraqi marine and coastal waters, Northwestern Arabian Gulf - Nasir, N.A.; Al-Najar, G.A (Mesopotamian Journal of Marine Sciences, 2022)
This study was carried out during the period from Winter 2010 to Winter 2011 to evaluate the concentrations of heavy metals (Fe, Co, Ni, Cu and Pb) in tissues of commercially valuable coastal fishes (Talang Queenfish, Scomberoides commersonianus) from Iraqi coastal areas around the Faw Peninsula which receives petrochemical wastes. Thus, it is important to identify the extent of concentrations of heavy metals in fish and consider potential impacts on the food chain and risks to human health. Fe had the highest level of accumulation in the four tissues examined (gill, muscle, liver and gonad) of S. commersonianus whilst Pb had the lowest (p < 0.05). The order of the heavy metal concentrations in the gills, muscles, liver and gonad tissues of S. commersonianus across all the stations was Fe (198.27 μg/g) > Co (21.07 μg/g) > Cu (7.89 μg/g) > Ni (5.43 μg/g) > Pb (1.85 μg/g). This study suggests that additional measures must be taken to monitor waste and ambient water quality, and to prevent contamination of fish for human consumption